SIMULACRUM DAN EKSTASI KOMUNIKASI DALAM NARASI FILM SPIN-OFF - A. Yudo Triartanto (Jurnal Komunikasi, 2015)
Movie spin-off continue to be produced. The narrative contains a number of characters are distanced from the world of reality. As a result, the film spin-off into an ecstasy of communication and communication simulacrum. The character into a anomalus, which is difficult to categorize the humanity in the usual categories. Characters that live only in the cinema screen as a simulacrum and the ecstasy of communication.